2022
DOI: 10.1017/s0954422422000142
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E deficiency in childhood: a narrative review

Abstract: Vitamin E is an important nutrient from the earliest stages of life. It plays key roles as an antioxidant and in the maintenance of the immune system, among others. Vitamin E deficiency (VED), which occurs more frequently in children, is rarely addressed in the literature. This narrative review aims to summarize the chemistry, biology, serum indicators, and clinical trials that have evaluated the impact of fortification and other relevant aspects of vitamin E, in addition to the prevalence of its deficiency, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 102 publications
0
1
0
Order By: Relevance
“…Vitamin E is the general name of 4 tocopherols and 4 tocotrienols found in food [ 33 , 34 , 35 ], which is known for its antioxidant activity, is essential for growth and development, and is closely related to immune function [ 36 , 37 , 38 ]. Relevant studies have shown that VE deficiency mainly leads to nervous system abnormalities, anemia, cardiovascular diseases, pneumonia, and asthma [ 39 , 40 ]. An excessive intake of VE will resist the effect of vitamin K, resulting in bleeding, platelet generation, and aggregation and thus thrombosis [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E is the general name of 4 tocopherols and 4 tocotrienols found in food [ 33 , 34 , 35 ], which is known for its antioxidant activity, is essential for growth and development, and is closely related to immune function [ 36 , 37 , 38 ]. Relevant studies have shown that VE deficiency mainly leads to nervous system abnormalities, anemia, cardiovascular diseases, pneumonia, and asthma [ 39 , 40 ]. An excessive intake of VE will resist the effect of vitamin K, resulting in bleeding, platelet generation, and aggregation and thus thrombosis [ 41 ].…”
Section: Discussionmentioning
confidence: 99%